(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Teaching the formation of mathematical symbols for children emphasizes that educating and guiding children in mathematics from an early age is very important to help them develop logical thinking, creativity, and problem-solving skills. The research results have presented how teachers can apply the method of learning through games and practical activities to help children understand and form mathematical symbols naturally and effectively. Mathematics education for children is not just about learning formulas or memorizing concepts, but it needs to help children understand and form mathematical symbols in their minds naturally and flexibly. At the same time, the application of learning methods through games and practical activities will help children approach mathematics in an interesting and non-boring way, thereby arousing their passion and love for this subject. The study was conducted on 515 children aged 4-5 years. This research highlights the importance of early mathematics education and the use of innovative teaching methods to engage young children and help them develop fundamental mathematical skills. By creating a fun and stimulating learning environment, children can develop an interest in mathematics that will stay with them throughout their academic careers.